2018
DOI: 10.1097/jom.0000000000001327
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interrupting Sedentary Behavior on the Cardiometabolic Health of Adults With Sedentary Occupations

Abstract: Sitting time was lower during the message-receiving period, but the difference between groups was no longer apparent after the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Similarly, there are several studies that show that the use of messages through the smartphone aimed at enhancing the levels of PA in users is effective, since sedentary lifestyles can be reduced through reminders on the smartphone to get up when the user has been sitting for a long time, to go for a walk or do any simple exercise (McCoy et al, 2017; Dunning et al, 2018). Through virtual reality, some aspects related to PA can be improved more effectively, such as spatial orientation (Gómez-García et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are several studies that show that the use of messages through the smartphone aimed at enhancing the levels of PA in users is effective, since sedentary lifestyles can be reduced through reminders on the smartphone to get up when the user has been sitting for a long time, to go for a walk or do any simple exercise (McCoy et al, 2017; Dunning et al, 2018). Through virtual reality, some aspects related to PA can be improved more effectively, such as spatial orientation (Gómez-García et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10 studies investigating the chronic cardiovascular responses to breaks or reductions in sitting time were found ( Table 3 ), where 6 studies were randomized controlled trials and 4 were non-randomized non-controlled trials. The studies included healthy 47 48 49 50 51 52 , overweight/obese 53 54 and rheumathoid arthritis 55 subjects, with a specific study including both healthy and non-healthy adults 56 , with sample sizes ranging from 12 to 264. Also, the duration of interventions varied from 10 weeks up to 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used long-term strategies aimed at sitting reduction or sitting breaks throughout the day, usually through constant reminders of the importance of sitting breaks in the work environment, with some studies also using treadmill walking workstations. In order to verify the chronic cardiovascular responses to these interventions, studies evaluated blood pressure 47 48 49 50 51 53 54 55 56 , mean arterial pressure 52 and biomarkers 47 48 49 51 53 55 . TESTEX scores from the studies ranged from 3 to 10, with an average score of 7, indicating moderate quality, where only one study reached 10 points in the scale 54 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is still a paucity of evidence on the effect of workplace health programmes to reduce sedentary behaviour (Hadgraft et al 2020 ). Thus far, only one LMIC intervention study has demonstrated a drop in sedentary behaviour amongst office workers, by using tailored mobile text messages to interrupt sitting time (Dunning et al 2018 ). Messages reminding the study participants in the intervention group to stand up and take regular short walks were sent every 20 min during working hours in the working week, for the duration of the 10-week trial.…”
Section: Introductionmentioning
confidence: 99%